Genotypic Variability in Some Morpho-Physiological Traits in Different Environments and Their Relationship with Cassava (Manihot esculenta Crantz) Root Yield - Joseph Adjebeng-Danquah; Isaac Kwadwo Asante; Joseph Manu-Aduening; Richard Yaw Agyare; Vernon Edward Gracen; Samuel Kwame Offei (International Journal of Agronomy)
Cassava root yield under diverse environments is influenced by morpho-physiological traits that are in turn influenced by genotype, environment, and genotype × environment interaction (GEI). Most GEI analyses in cassava have been limited to root yield with less emphasis on stability of other yield-related traits. This study was carried out to assess the effect of GEI on some morpho-physiological traits in cassava and key traits that are useful for selection in different environments. The study utilized 20 cassava genotypes evaluated in six environments, namely, Fumesua 2013 and 2014, Nyankpala 2013 and 2014 (irrigation), and Nyankpala 2013 and 2014 (no irrigation). The genotypes were arranged in a randomized complete block design (RCBD) with three replications and assessed for a number of morpho-physiological traits, root yield and yield components. The data were subjected to analysis of variance using SAS statistical package. Subsequently, the GGE biplot was used to carry out genotype × environment, genotype × trait, and environment × trait interaction analyses to determine the specificity of genotypic performance and traits linked to particular environments. The results indicated significant (P<0.05) GEI effect on all traits except leaf temperature. The genotype × trait biplot analysis revealed closely related traits and those associated with root yield and genotypes that show weakness in these traits. Both environment × trait biplot and principal component analyses identified traits with higher discriminatory power among genotypes in various environments particularly in the dry environments. These can be used as secondary traits to select drought-tolerant genotypes. From this study, the GGE biplot was useful in identifying traits associated with specific genotypes in different environments to aid in selection. Moderate broad-sense heritability estimates werefound for storage root yield, harvest index, plant height, ratio of storage rootlength to girth, and cassava mosaic disease score indicating that progresscan be made through selection for these traits.